Konsep Keadilan dalam Perspektif Filsafat Hukum Islam - Amin, Mahir (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article discusses about the concept of justice in the perspective of the philosophy of Islamic law. Philosophically, there are two formulations of justice: first, the view that what is meant by justice is a harmony between the use of right and obligation are in line with the implementation of the proposition of the balance of law or the dose of right and obligation; second, the view of the lawyers who formulate that justice is a harmony between legal certainty and proportionality of law. Justice, in Islamic law, is derived from the Most Just. It is because Allah SWT is the upholder of justice, then He must be believed not to apply unjust to His servants. The concept of justice, based on al-Shatibis maqasid al-shariah theory, is determined by the benefits which are divided into three, namely daruriyyat (necessities), hajiyyat (needs), and tahsiniyyat (luxuries). This indicates that Islam is concerned with the issue of justice. The conception of justice will continue to evolve in line with the social development. Construction of law and justice in Islam cannot be separated from morality and transcendental beliefs since these aspects are intertwined. Keywords: Justice, philosophy, law, Islam.